The Role of Education as a Moderator in the Relationship Between Financial Literacy and Social Environment on Gen Z Consumption Behavior in the Special Region of Yogyakarta - Indah Sari; Denies Priantinah (FKIP, Universitas Palangka Raya, 2025)
This study aims to determine the role of education as a moderation variable in the relationship between financial literacy and social environment on the consumption behavior of Gen Z in the Special Region of Yogyakarta. The research method used is a quantitative approach with a descriptive quantitative method. The study sample consisted of 400 Gen Z respondents aged 14-29 years, selected using purposive sampling through questionnaires. Data analysis was conducted using Partial Least Square (PLS) with Structural Equation Modeling (SEM) through the SmartPLS 4.0 application. The results showed that financial literacy significantly influences consumption behavior (p-Value 0.001 < 0.05), while the social environment does not have a significant influence (p-Value 0.105 > 0.05). Additionally, education does not moderate the relationship between financial literacy and consumption behavior (p-Value 0.635 > 0.05) or the relationship between the social environment and consumption behavior (p-Value 0.244 > 0.05).